Comparative perspectives on alternative dispute resolution: with reference to Malaysia - Abdul Hak, Nora; Oseni, Umar Aimhanosi; Mohamed, Nurah Sabahiah (IIUM Press, 2016)
This textbook explains various ADR processes such as mediation, arbitration, the role of the ombudsman and expert opinion. An examination of ADR in Islamic Law such as sulh, tahkim and muhtasibis also undertaken as ADR is an integral part of Islamic law, and it is as old as Islam itself. The concept of court annexed mediation and the development of its application is also discussed. Other topics included in this book are the Arbitration Act 2005 with reference to the powers of the court, construction disputes resolution and mediation in family disputes. This textbook is co-authored by three law lecturers of Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia,Dr. Nora Abdul Hak, Dr. Umar A. Oseniand Dr. NurahSabahiah Mohamed. This book is a useful reference for law students, academicians, practitioners and the general public